1995
DOI: 10.1136/adc.73.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Co-trimoxazole induced aseptic meningitis.

Abstract: A 15 year old boy presented with two episodes of aseptic meningitis-like reactions after ingestion of co-trimoxazole. The diagnosis of co-trimoxazole induced aseptic meningitis was made. This syndrome should be considered in the differential diagnosis of aseptic meningitis. (Arch Dis Child 1995; 73: 257-258)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Although high leukocyte count, normal glucose, and elevated protein CSF levels are usually observed in patients with aseptic meningitis, Matsuura-Otsuki et al 14 reported normal CSF findings of a patient with psoriatic arthritis who developed infliximab-associated aseptic meningitis. 15 Pashankar et al 16 also found normal CSF results in a child that presented with aseptic meningitis after co-trimoxazole treatment. It has been reported that many drugs lead to aseptic meningitis.…”
Section: Discussionmentioning
confidence: 93%
“…Although high leukocyte count, normal glucose, and elevated protein CSF levels are usually observed in patients with aseptic meningitis, Matsuura-Otsuki et al 14 reported normal CSF findings of a patient with psoriatic arthritis who developed infliximab-associated aseptic meningitis. 15 Pashankar et al 16 also found normal CSF results in a child that presented with aseptic meningitis after co-trimoxazole treatment. It has been reported that many drugs lead to aseptic meningitis.…”
Section: Discussionmentioning
confidence: 93%
“…Many drugs have been associated with aseptic meningitis (Table 4 1,2,5,79 ), and the diagnosis is mainly one of exclusion. 1,2 The intensity of symptoms can vary and can appear anywhere from 4 hours to 4 months after the use of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to note the time of symptom onset with regard to the beginning of the drug therapy. 1,2,5,7,9…”
Section: Discussionmentioning
confidence: 99%